Monitoring the Environment Exposed to Road Waste - Chelnokov, Vitaliy V.; Matasov, Aleksey V.; Zabolotnaya, Elena; Makarova, Anna S.; Glushko, Andrey N. (KnE Life Sciences, 2022)
This study aimed to carry out a systematic analysis of the literature on the environmental impactsof waste resulting from year-round maintenance of roads (WMR) with deicing agents. The impacts on economic factors and the environment at all stages of the life cycle were systematically examined, taking into account the engineering and technological efficiencies, and the direct, indirect, prolonged and deferred effects. A structural-integral block-hierarchical model for monitoring and evaluating the impacts of WMR on the environment and on the industrial, social and economic system as a whole was developed.This incorporated the complex spatial-temporal industrial, biological, physical and chemical impacts of elements of the road infrastructure itself, as well as external conditions. Keywords: pollution monitoring, environmental impact of waste, pollution from transport